Managing global competitive dynamics - Peng, Mike; Gokalp, O. (2011)
Global competitive dynamics refers to the actions and responses undertaken by competing firms around the world. Since one firm's actions are rarely unnoticed by rivals, the initiating firm would naturally like to predict rivals' responses before making its own move. This process is called competitor analysis, advocated a long time ago by the ancient Chinese strategist Sun Tzu's teaching to "know yourself"' and "know your opponents." As military officers have long known, a good plan never lasts longer than the first contact with the enemy because the enemy foes not act according to our plan (!). Thus, the defining feature of competitive dynamics is action, but not plan. This chapter first highlights the "strategy as action" perspective, followed by a "strategy tripod" model on global competitive dynamics. Then, how to cooperate and signal is outlined, with one interesting extension on how local firms fight multinational enterprises (MNEs) in emerging economies. Debates, extensions, and managerial implications follow.